Elucidating the role of hyperglycaemia in endothelial cell and pericyte morphology, function and crosstalk, and blood-brain barrier integrity - Hashmat, Arshad (2024)
Diabetes is a complex metabolic disorder associated with a myriad of neurovascular complications, including disruption of the blood-brain barrier (BBB) and endothelial dysfunction. The intricate relationship between hyperglycaemia and cells of the neurovascular unit is of significant importance and yet remains inadequately understood. This study aims to delve into the impact of elevated glucose levels on three key areas: endothelial cell function, pericyte-endothelial interaction, and the integrity of the BBB in vitro.